A new online detector for estimation of peripheral neutron equivalent dose in organ. Issue 11 (30th October 2014) - Irazola, L.; Lorenzoli, M.; Bedogni, R.; Pola, A.; Terrón, J. A.; Sanchez‐Nieto, B.; Expósito, M. R.; Lagares, J. I.; Sansaloni, F.; Sanchez‐Doblado, F.
Abstract : Purpose: Peripheral dose in radiotherapy treatments represents a potential source of secondary neoplasic processes. As in the last few years, there has been a fast‐growing concern on neutron collateral effects, this work focuses on this component. A previous established methodology to estimate peripheral neutron equivalent doses relied on passive (TLD, CR39) neutron detectors exposed in‐phantom, in parallel to an active [static random access memory ( SRAMnd )] thermal neutron detector exposed ex‐phantom. A newly miniaturized, quick, and reliable active thermal neutron detector ( TNRD, Thermal Neutron Rate Detector) was validated for both procedures. This first miniaturized active system eliminates the long postprocessing, required for passive detectors, giving thermal neutron fluences in real time. Methods: To validate TNRD for the established methodology, intrinsic characteristics, characterization of 4 facilities [to correlate monitor value (MU) with risk], and a cohort of 200 real patients (for second cancer risk estimates) were evaluated and compared with the well‐established SRAMnd device. Finally, TNRD was compared to TLD pairs for 3 generic radiotherapy treatments through 16 strategic points inside an anthropomorphic phantom. Results: The performed tests indicate similar linear dependence with dose for both detectors, TNRD and SRAMnd, while a slightly better reproducibility has been obtained for TNRD (1.7% vs 2.2%). Risk estimates when delivering 1000 MU are in good agreement between both detectors (mean deviation of TNRD measurements with respect to the ones of SRAMnd is 0.07 cases per 1000, with differences always smaller than 0.08 cases per 1000). As far as the in‐phantom measurements are concerned, a mean deviation smaller than 1.7% was obtained. Conclusions: The results obtained indicate that direct evaluation of equivalent dose estimation in organs, both in phantom and patients, is perfectly feasible with this new detector. This will open the door to an easy implementation of specific peripheral neutron dose models for any type of treatment and facility.